The transistor laser. - Holonyak, N., Jr.
A research team at the University of Illinois at Urbana-Champaign has developed a new, more powerful kind of device, called the transistor laser. The transistor puts out both electrical signals and a laser beam, which can be directly modulated to send optical signals at the rate of 10 billion bits per second. With some further modification, the transistor laser will eventually send a staggering 100 billion bits per second or more. Instead of using relatively slow wires to connect chips stacked together in packages, transistor lasers can be used as optical interconnects, which would let data flow instantaneously to and from memory chips, graphics processors, and microprocessors. There is much work ahead, but unlike the host of self-assembling, blue-sky nanotechnologies currently being touted as the next big thing in optoelectronics, transistor lasers do not need an entirely new fabrication infrastructure for further development or even to go into production.
Keywords: University of Illinois; Blue-sky nanotechnologies; Electrical signals; Fabrication infrastructure; Graphics processors; Laser beam; Memory chips; Microprocessors; Optical interconnects; Transistor lasers